The read aloud cloud : an innocent's guide to the tech inside - Brazeal, Forrest (Wiley, 2021)
Have you ever imagined the internet as a giant Rube Goldberg machine? Or the fast-evolving cloud computing space as a literal jungle filled with prehistoric beasts? Does a data breach look like a neo-noir nightmare full of turned-up coat collars and rain-soaked alleys? Wouldn't all these vital concepts be easier to understand if they looked as interesting as they are? And wouldn't they be more memorable if we could explain them in rhyme? Whether you're a kid or an adult, the answer is: YES! The medicine in this spoonful of sugar is a sneaky-informative tour through the past, present and future of cloud computing, from mainframes to serverless and from the Internet of Things to artificial intelligence. Forrest is a professional explainer whose highly-rated conference talks and viral cartoon graphics have been teaching engineers to cloud for years. He knows that a picture is worth a thousand words. But he has plenty of words, too.